2008
DOI: 10.1111/j.1600-6143.2008.02384.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Portopulmonary Hypertension: Mayo Clinic Experience Categorized by Treatment Subgroups

Abstract: To determine the natural history of portopulmonary hypertension (POPH), a retrospective screening-right heart catheterization-survival analysis of patients was performed. We categorized patients by three treatment subgroups: (1) no therapy for pulmonary hypertension (PH) or liver transplantation (LT), (2) therapy for PH alone and (3) therapy for PH followed by LT. Seventyfour patients were identified between 1994 and 2007. Nineteen patients received no therapy for PH and no LT representing the natural history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
229
1
19

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(250 citation statements)
references
References 21 publications
1
229
1
19
Order By: Relevance
“…Therefore, a sPAP greater than 50 mmHg at ECHO represents the cut-off point for executing a RHC. At RHC, a mPAP greater than 45 mmHg represents a contraindication to TIPS [24,[70][71][72][73][74]79]. …”
Section: Cardiac Dysfunctionmentioning
confidence: 99%
“…Therefore, a sPAP greater than 50 mmHg at ECHO represents the cut-off point for executing a RHC. At RHC, a mPAP greater than 45 mmHg represents a contraindication to TIPS [24,[70][71][72][73][74]79]. …”
Section: Cardiac Dysfunctionmentioning
confidence: 99%
“…Swanson and coworkers demonstrated that patients with medically treated PH and OLT had a better 5-year survival (67%) than patients treated only pharmacologically without OLT (45%). 6,11 However, unless patients with preserved RVF demonstrated a good response to vasodilator therapy, OLT was associated with a poor outcome. 6 The pharmacologic therapy of PH usually should be continued for several months after OLT.…”
Section: Discussionmentioning
confidence: 99%
“…39 Historically, patients with POPH have been recognized as having very high risk for OLT with unacceptably increased morbidity and mortality. 11,[40][41] During the past 10 to 15 years, newer medications and aggressive perioperative treatment have enabled centers to successfully transplant these patients. However, there remain specific medical requirements that must be met before these patients are considered candidates for transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) The prognosis of PPHTN is very poor, 2) and the pathogenesis and management of PPHTN are not well understood.…”
mentioning
confidence: 99%